Enrique’s Journey: The Perilous Quest of Undocumented Migrants for a Better Life - Sharma, Manahari (Journal of Development Review, 2024)
In this article, an attempt is made to analyse the plight and predicament of illegal migrants crossing the Mexican border to reach the USA for a better life. Sonia Nazario’s Enrique‘s Journey is an account of a child protagonist Enrique, who travels from Honduras to North America through deadly routes to meet his mother and becomes the subject of an unjust border. Children like Enrique and other millions of migrants from underdeveloped countries like Honduras, Guatemala, and El Salvador undergo a arrowing experience when they cross the border to escape from civil war, impunity, and poverty in their countries. At the border, the inherent rights of all human beings with the promise of true democracy become meaningless: refugees and undocumented migrants are victimised by national sovereignty policy and compelled to live bare lives. In this paper, I will attempt to analyse the problems of displaced people based on different grounds: Who are undocumented migrants? What is the cause behind forceful exit from their own country? Why have they been encountering unspeakable suffering while crossing the border? How is the matter of hospitality understood? Do they find themselves in a safer zone and freedom in an unwelcome space? Such questions are discussed using theories on migrants and refugees.